Chandra Detects Low-luminosity Active Galactic Nucleus with MBH = 104–106 M⊙ in Nearby (z < 0.5) Dwarf and Star-forming Galaxies - Mainak Singha; Julissa Sarmiento; Sangeeta Malhotra; James E. Rhoads; L. Y. Aaron Yung; Junxian Wang; Zhen-Ya Zheng; Ruqiu Lin; Keunho Kim; Jialai Kang; Santosh Harish (The Astrophysical Journal)
We searched the Chandra and XMM archives for 900 Green Pea galaxies to identify signs of active galactic nuclei (AGN). Green peas are low-mass, emission-line galaxies that resemble high-redshift dwarf galaxies. From 29 observations, we detected X-rays in nine galaxies with signal-to-noise ratio > 3. These X-ray sources also show He ii and broad H α emissions, suggesting winds, though the weak correlation between their line widths implies that the He ii emission is not from super-Eddington accretors. The ratio of X-ray luminosity to star formation rate aligns with an anticorrelation with metallicity for most detected sources, pointing to ultraluminous X-ray sources as likely contributors. The X-ray emission exceeds what stellar processes can produce, supporting the existence of low-luminosity AGN. Using the broad H α emission lines, we infer black hole masses ranging from 10 ^4 to 10 ^6 M _⊙ in these sources. Since Green Peas are significant Lyman continuum leakers, these AGN may have played a role in cosmic reionization.